Evaluation of mutants for bold seed and high yield in niger (Guizotia abyssinica L.): Evaluation of mutants for bold seed and high yield in niger (Guizotia abyssinica L.) - SUVARNA,; B V TEMBHURNE,; V RACHAPPA HAVER,; J R DIWAN, (Journal of Oilseeds Research, 2020)
Two varieties RCR 18 and DNS 17 of niger were irradiated with different doses of gamma rays viz., 150Gy, 175 Gy, 200 Gy, 225 Gy, 250 Gy and 275 Gy. The M1 generation along with control was evaluated during rabi 2016. The LD 50 dose was found to be 250 Gy for DNS 17 and 275 Gy for RCR 18. Mutants showed variations for plant height, number of branches/plant, number of capitula/plant in both the varieties. Control showed maximum seed weight/plant (1.7360 g) in DNS 17. But in RCR 18, mutants irradiated with 150 Gy showed maximum seed weight/plant (3.92280 g) followed by 250 Gy (3.1334 g).